PENGEMBANGAN ASESMEN KESULITAN BELAJAR UNTUK MENGUNGKAP KESULITAN BELAJAR MAHASISWA CALON GURU BIOLOGI - Juhanda, Aa (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2017)
Abstract This study aims to obtain a description of the mastery of the concept of biology teacher candidates through the study of learning difficulties in the concept of development stage of animal embryo. The subjects of the study were 43 students of semester 6 of academic year 2013 which contracted embryology subjects. The instruments used consist of diagnostic questions (essays and multiple choice questions) and interview format. Data analysis was done quantitatively and qualitatively. The results showed that the mastery of the concept of students on aspects of C1 (remember) is 53% (enough); C2 (understanding) of 77% (good); C3 (applying) of 98% (excellent); And C4 (analyze) of 58% (enough). In addition, some students who experienced difficulty showed a positive response to their learning difficulties.Keywords: Assessment of Learning Difficulties, Concept Mastery, Stages of Animal Embryology Development